Integration of Gamification and Health Belief Model to Promote Dental Health in School Children: A Narrative Review for Digital Intervention Development - Abigayl, Ivana; Adiatman, Melissa (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Dental caries is one of the most common health problems among school-aged children and can have long-term impacts on their quality of life. Most oral health promotion interventions to date remain conventional and are often unappealing to children. On the other hand, advancements in digital technology offer significant opportunities for developing more interactive and engaging educational approaches. Review: This literature review aims to analyze the relevance and effectiveness of integrating the Health Belief Model (HBM) with gamification in the development of digital interventions for school-aged children in the field of oral health. The literature findings indicate that HBM-based interventions are effective in enhancing children’s perceptions of susceptibility, benefits, and self-efficacy in maintaining oral health. Gamification has been shown to improve engagement and motivation through game elements such as points, challenges, and rewards. Several studies conclude that, although each approach has its own strengths, the strategic integration of HBM and gamification can address their respective limitations—particularly in achieving long-term behavior change. Conclusion: However, most digital interventions have not yet explicitly incorporated all components of the HBM, nor have they adequately addressed local contexts such as culture, technological access, and the role of teachers and parents. Therefore, there is a need for the design of digital intervention applications based on HBM and gamification through a co-design approach. This concept holds potential as a direction for further research in developing sustainable and evidence-based oral health promotion solutions in Indonesia.